Interactive Effect of Tillage and Phosphate Fertilizers in Conjunction with FYM to Sorghum+Greengram Intercropping System on Performance of Crops - Laddha, K C; Totawat, K L (Annals of Arid Zone, 2016)
Disc ploughing gave significantly higher grain and stover yields of sorghum, green gram and sorghum equivalent under semi-arid agro-ecoregion of Rajasthan. Incorporation of lOt ha -1 FYM and phosphorus upto 30 kg ha -1 increased grain and stover yields of intcrcrops and sorghum equivalent as well. Uptake of N, P and K by the crops under intercrop system increased when different tillage practices were followed in conjunction with 10 t ha -1 FYM and 30 kg P205 ha-1.